2023
DOI: 10.1088/1361-6501/acf8e3
|View full text |Cite
|
Sign up to set email alerts
|

A deep neural network with electronic nose for water stress prediction in Khasi Mandarin Orange plants

Chayanika Sharma,
Nairit Barkataki,
Utpal Sarma

Abstract: Water stress is a significant environmental factor that hampers plant productivity and leads to various physiological and biological changes in plants. These include modifications in stomatal conductance and distribution, alteration of leaf water potential & turgor loss, altered chlorophyll content, and reduced cell expansion and growth. Additionally, water stress induces changes in the emission of volatile organic compounds across different parts of the plants. This study presents the development of an el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Enabling it to extract more complex features as the network deepens can help improve the accuracy of the prediction. Therefore, it is widely used to predict crop yield and fruit characteristics in many plants, including corn yield [ 70 73 ], firmness, soluble solids content (SSC) and growth characteristics of apple [ 73 , 74 ], the volume of carrot and apple [ 75 , 76 ], classification in bananas [ 77 ], the incidence of the blister moth in leaves of apple [ 78 ], stress response in orange [ 79 ]. These studies have demonstrated the effectiveness and reliability of deep learning models.…”
Section: Discussionmentioning
confidence: 99%
“…Enabling it to extract more complex features as the network deepens can help improve the accuracy of the prediction. Therefore, it is widely used to predict crop yield and fruit characteristics in many plants, including corn yield [ 70 73 ], firmness, soluble solids content (SSC) and growth characteristics of apple [ 73 , 74 ], the volume of carrot and apple [ 75 , 76 ], classification in bananas [ 77 ], the incidence of the blister moth in leaves of apple [ 78 ], stress response in orange [ 79 ]. These studies have demonstrated the effectiveness and reliability of deep learning models.…”
Section: Discussionmentioning
confidence: 99%
“…The larger the receptive field of the neuron the higher the quality of the image needed, while more parameters are required to participate in the convolution operation as the depth of the network deepens [28][29][30][31][32]. In addition, traditional convolution operations use the same processing for all spatial dimensions of the input feature maps, which means that performing convolution operations on high-resolution feature maps can be very expensive.…”
Section: Gmfe Modulementioning
confidence: 99%
“…They used invasive and destructive methods, where leaf samples were cut with scissors into square pieces measuring approximately 1 cm by 1 cm and placed in the sample holder. To evaluate the signal from the E-Nose was used classifier models such as bagging k-nearest neighbors (KNN Bag), adaptive boosting (AdaBoost) decision tree (ABDT) (Hazarika et al, 2020) and deep neural network (DNN) (Sharma et al, 2023).…”
Section: Introductionmentioning
confidence: 99%